Factors affecting liposomes particle size prepared by ethanol injection method - Sherif Shaker; Ahmed Rifaat Gardouh; Mamdouh Mostafa Ghorab (Wolters Kluwer Medknow Publications, 2017)
Ethanol injection is one of the techniques frequently used to produce liposomes which favors both simplicity and safety. In this process, an ethanolic solution of lipids is rapidly injected into an aqueous medium through a needle, dispersing the phospholipids throughout the medium and promoting the vesicle formation. Being a critical parameter that determines the fate of liposome and its distribution, we studied different factors affecting the particle size of liposomes including different phospholipid (Phosal® 53 MCT) and cholesterol concentrations and the use of different types of non-ionic surfactants at fixed Phosal® 53 MCT concentration of 50 mg per formulation. Both Phosal® 53 MCT and cholesterol concentration had direct effect on liposomes particle size. Non-ionic surfactants produced liposomes of smaller particle size when compared to conventional liposomes formed using Phosal® 53 MCT 300 mg per formulation only, whereas this effect was diminished when higher Phosal® 53 MCT to cholesterol ratios were used that obviously increased liposomes size. Smaller liposomes sizes were obtained upon using non-ionic surfactants of lower hydrophilic/hydrophobic balance (HLB) as both Tween 80 and Cremophor RH 40 produced liposomes of smaller particle size compared to Poloxamer 407. The smallest liposomes particle size was successfully obtained in the formulation comprising 300 mg Phosal® MCT, 150 mg cholesterol and 50 mg Tween 80.